TE-N2 Laser by Using Low Inductance Capacitor - Hussein, Mohammed T. (Nahrain University College of Engineering Journal, 2009)
The design, construction and operation of a transversely excited N2 laser using low inductance capacitors, is presented, the laser pulse generation is 1200?J with pulse width 8ns when operated at about 30mbar with applied voltage of 15-30 kV. The system is capable of giving 150 kW peak power. The best values ofspecific energy and breakdown voltage are 0.03 J/L and 600 V/cm-mbar respectively